Austria : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2005)
This Selected Issues paper estimates a dynamic model of foreign currency loans to households in Austria to analyze their behavior and assess the effectiveness of measures intended to stem their rise. This paper also studies the developments in Austria's economic linkages with Germany and the Central and Eastern European countries (CEECs). It finds that there has been delinking from Germany, albeit measured, while economic relationships with key CEEC trading partners have become stronger. The paper also discusses the dynamics of Austria's economic linkages with Germany, and examines these linkages with the CEECs.